Arti Persaudaraan Menurut Paus Fransiskus dan Gus Dur - Widiasena, Stefanus Albert Putra (Fakultas Teologi, Universitas Sanata Dharma, 2024)
In the midst of the weakening of fraternal relations between people, there are two important figures who write their ideas related to